2008
DOI: 10.1159/000114827
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Consultation Behavior of Self-Reported Rectal Bleeding by Face-to-Face Interview in an Asian Community

Abstract: Background and Aim: Although rectal bleeding is a common gastrointestinal symptom, there are very few community-based studies, and all of these studies were conducted in the West. So far the epidemiologic characteristics of rectal bleeding have not been defined in an Asian country. We aimed to characterize self-reported rectal bleeding and its association with functional bowel disorders in Turkey. Factors affecting healthcare-seeking behavior were reviewed as well. Subjects and Methods: In this study, 760 subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Chronic diarrhoea is a common complaint in the general population in community-based surveys (3,4). More than one-in-four individuals with chronic diarrhoea will consult a physician (5), and a proportion of these individuals will be referred on for further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic diarrhoea is a common complaint in the general population in community-based surveys (3,4). More than one-in-four individuals with chronic diarrhoea will consult a physician (5), and a proportion of these individuals will be referred on for further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…(5-7) However, chronic diarrhea is common in the community, affecting between 2% and 9% of individuals. (8)(9)(10)(11) In population-based surveys such as these, the majority of people will have functional bowel disease, with no underlying organic cause. Despite this, many patients will be referred for colonoscopy, because diarrhea is an alarm symptom that is thought to be indicative of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have reported epidemiologic differences in the causes of lower gastrointestinal bleeding between Eastern and Western populations 1216 . Basaranoglu and colleagues interviewed roughly 700 patients in Turkey, aged 18 to 86, where 79 had rectal bleeding and 43 sought medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-one percent received sigmoidoscopy and 16% received double-contrast barium enema. Biopsies were not included in the evaluation, leaving suspicion for wrong diagnoses or missed malignancy 12 . In a study out of New Delhi, 240 patients with rectal bleeding all received a colonoscopy, and non-specific colitis and ulcers were the predominant diagnoses.…”
Section: Discussionmentioning
confidence: 99%